2019
DOI: 10.3390/f11010025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Mapping Green Areas Ecosystem Services and Socio-Demographic Characteristics in Turin Neighborhoods (Italy)

Abstract: The ecosystem services (ES) and human well-being are keywords that guide the Italian strategy on urban greening. The development of ES priorities linked to specific land uses help to guide the drafting of management plans. The aim of the research was to assess and map green areas ecosystem services and socio-demographic characteristics in Turin neighborhoods in order to identify where to improve the provision of ecosystem services and the socio-demographic conditions. The Preliminary Assessment Method (PAM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The overview of the weight factors used to describe potential link intensity between ES group (provisioning, regulating, cultural) and individual WB components are shown in Table 1. The MEA approach and the assumed strengths of the linkages between ES and WB can be partially supported by the review literature, which indicates that the most frequently assessed urban ES are from the categories of regulation and maintenance [15,34] or provision [29], suggesting that these ES categories are perceived to have the most important impacts on WB. The strength of the connection between ES and WB (weak, medium, and strong) was taken from the MEA, but is to some extent supported by the literature review.…”
Section: Theoretical Approachmentioning
confidence: 92%
See 2 more Smart Citations
“…The overview of the weight factors used to describe potential link intensity between ES group (provisioning, regulating, cultural) and individual WB components are shown in Table 1. The MEA approach and the assumed strengths of the linkages between ES and WB can be partially supported by the review literature, which indicates that the most frequently assessed urban ES are from the categories of regulation and maintenance [15,34] or provision [29], suggesting that these ES categories are perceived to have the most important impacts on WB. The strength of the connection between ES and WB (weak, medium, and strong) was taken from the MEA, but is to some extent supported by the literature review.…”
Section: Theoretical Approachmentioning
confidence: 92%
“…Further, instead of referring to WB as one lump phenomenon, it focuses on individual WB components and provides a weighted link between separate ES categories and individual WB components. In this respect, the approach we used could be further developed to evaluate the contribution of UGI to WB through ES using WB indicators and objectivize WB evaluation using literature review, field research, spatial analysis involving GIS and remote sensing, land use, landscape metrics, or statistical methods [26][27][28][29][30][31]. Finally, unlike most of the studies reviewed, the approach undertaken in our research focuses on a comprehensive list of ESs.…”
Section: Implication For Planning and Limitations Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these spaces provide many ecological, psychological, and social benefits [7,8]. For example, in 2020, Battisti et al [9] showed that in an urbanized context (City of Turin) the ecosystem services provided by public green areas differed among neighborhoods and were related with socio-demographic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Natural elements, including those in cities, e.g., roadside trees or green areas, affect the level of air pollution. The absorption of gaseous and particulate matter pollutants is one of the regulating services provided by the environment, whose effectiveness and benefits have been estimated by research conducted around the world [3][4][5]. The parameters of the impact of various tree species growing in urban areas on air quality were determined e.g., in [6].…”
Section: Introductionmentioning
confidence: 99%